2020
DOI: 10.1021/acs.jafc.0c03396
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxy-1,4-naphthoquinone Induces Metabolic Shifts in Penicillium Digitatum Revealed by High-Dimensional Biological Data

Abstract: Penicillium digitatum is the primary pathogen causing the green mold of citrus. The need for the development of higher effective and lower toxic natural antifungal agents is urgent, owing to the lack of antifungal agents that can successfully combat P. digitatum. Herein, the effects and mechanisms of 2-methoxy-1,4-naphthoquinone (MNQ) as a potential inhibitor of P. digitatumwere studied. First, MNQ showed a significant anti-P. digitatum effect with a minimum inhibitory concentration value of 5.0 μg/mL. Then, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…To deeply understand the action mechanism of nanoemulsion from molecular aspects and seek the pathway involved, we used RNA-Seq technology to profile the transcriptome of P. digitatum treated with nanoemulsion, which induced the expression of many stress response genes and the pathway involved to alleviate the adverse effect. Recent research by RNA-seq also observed different gene and pathway responses in P. digitatum cells treated by antifungal agent [( 41 , 42 )].…”
Section: Discussionmentioning
confidence: 99%
“…To deeply understand the action mechanism of nanoemulsion from molecular aspects and seek the pathway involved, we used RNA-Seq technology to profile the transcriptome of P. digitatum treated with nanoemulsion, which induced the expression of many stress response genes and the pathway involved to alleviate the adverse effect. Recent research by RNA-seq also observed different gene and pathway responses in P. digitatum cells treated by antifungal agent [( 41 , 42 )].…”
Section: Discussionmentioning
confidence: 99%
“…SEM observation was carried out on a scanning electron microscope (Zeiss, Oberkochen, Germany) to observe the morphology of P. italicum mycelia. SEM samples were prepared as described previously [ 6 ]. About 1.0 g of mycelia was collected from both treated and control media after 2 days of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, the resulting p values were adjusted using Benjamini and Hochberg’s approach for controlling the false discovery rate. Finally, p value < 0.05 and |log2 foldchange| > 1 were set as the criteria used for the screening of differentially expressed genes (DEGs) [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold values of '|log2 foldchange| > 1' and 'Padj < 0.05' were adopted to judge differently expressed genes (DEGs). 33 Finally, the enrichment analysis of the DEGs was performed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses.…”
Section: Transcriptome Profilingmentioning
confidence: 99%